1995
DOI: 10.1079/bjn19950072
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic detoxification of ammonia in the ovine liver: possible consequences for amino acid catabolism

Abstract: The effects of either low (25 pnollmin) or high (235 pnol/min) infusion of NH&l into the mesenteric vein for 5 d were determined on 0, consumption plus urea and amino acid transfers across the portaldrained viscera (PDV) and liver of young sheep. Kinetic transfers were followed by use of l5NH4C1 for 10 h on the fifth day with simultaneous infusion of [l-'3C]leucine to monitor amino acid oxidation.Neither PDV nor liver blood flow were affected by the additional NH, loading, although at the higher rate there was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
215
9
7

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(254 citation statements)
references
References 51 publications
22
215
9
7
Order By: Relevance
“…Isserty et al (1998) showed that the choice of the laboratory technique for PAH determination significantly influenced the calculated hepatic arterial/venous blood flows. In sheep, much lower hepatic arterial/venous blood flows (2% to 6%) were measured by Barnes et al (1986) using microspheres and by Lobley et al (1995) with PAH dilution (with the inclusion of a deacetylation step in the analysis). In the available dataset, different techniques were used for determination of PAH between Below Maintenance (where heating and acid deproteinisation was mostly used) and Above Maintenance (mainly dialysis method).…”
Section: Methodsmentioning
confidence: 91%
“…Isserty et al (1998) showed that the choice of the laboratory technique for PAH determination significantly influenced the calculated hepatic arterial/venous blood flows. In sheep, much lower hepatic arterial/venous blood flows (2% to 6%) were measured by Barnes et al (1986) using microspheres and by Lobley et al (1995) with PAH dilution (with the inclusion of a deacetylation step in the analysis). In the available dataset, different techniques were used for determination of PAH between Below Maintenance (where heating and acid deproteinisation was mostly used) and Above Maintenance (mainly dialysis method).…”
Section: Methodsmentioning
confidence: 91%
“…Ammonia produced in the rumen that is in excess of microbial requirement may be absorbed across the ruminal epithelium and converted to urea in the liver (Lobley et al, 1995), with the liver having the ability to remove ammonia added to the portal blood up to a maximum of 182 mg/min before peripheral blood concentrations increase (Symonds et al, 1981). It can therefore be concluded that in all three dietary treatments evaluated in this study, ammonia uptake by the portal drained viscera was well within the ability of the liver to metabolise it to urea.…”
Section: Discussionmentioning
confidence: 99%
“…When sheep are fed large quantities of a diet with a high percentage of RDP, as is the case for large lupin supplements, the concentration of ammonia in the circulation can reach toxic levels (Hungerford, 1990), especially if the intake of digestible carbohydrates is low (Hibbit, 1988). Although, lupins can supply large quantities of ME, unfortunately much of this energy is used for hepatic detoxification of the ammonia liberated in and absorbed from the rumen, particularly when large quantities of lupins are consumed each day (Lobley et al, 1995;Greaney et al, 1996).…”
Section: Levels Of Energymentioning
confidence: 99%